Evidence for s-channel single top quark production in pp collisions at √s = 1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Elsevier, 2013)
We present measurements of the cross sections for the two main production modes of single top quarks in pp- collisions at s=1.96 TeV in the Run II data collected with the D0 detector at the Fermilab Tevatron Collider, corresponding to an integrated luminosity of 9.7 fb-1. The s-channel cross section is measured to be σ(pp-→tb+X)=1.10-0.31+0.33 pb with no assumptions on the value of the t-channel cross section. Similarly, the t-channel cross section is measured to be σ(pp-→tqb+X)=3.07-0.49+0.54 pb. We also measure the s+t combined cross section as σ(pp-→tb+X,tqb+X)=4.11-0.55+0.60 pb and set a lower limit on the CKM matrix element |Vtb|>0.92 at 95% C.L., assuming mt=172.5 GeV. The probability to measure a cross section for the s channel at the observed value or higher in the absence of signal is 1.0×10-4, corresponding to a significance of 3.7 standard deviations. © 2013 Elsevier B.V.